2018
DOI: 10.5055/ajrt.2018.0171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance band exercise and reported life-satisfaction with older adults residing in a long-term care facility

Abstract: According to the Administration of Aging, 40.4 million (13.1 percent) of the US population or more than one in every eight Americans are 65 or older. Approximately 600 million people worldwide are aged 60 or older, and by 2050, this number will grow to 1.2 billion. Improvement and maintaining reported life-satisfaction can be linked to many co-occurring health benefits. The present manuscript addressing the potential life-satisfaction changes that seem to be associated with active participation in a chair resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Another study investigated the effect of resistance band exercise on older adults’ life satisfaction levels. The results indicated that older adults who participated in a 12-week resistance band exercise program had significantly higher life satisfaction levels [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study investigated the effect of resistance band exercise on older adults’ life satisfaction levels. The results indicated that older adults who participated in a 12-week resistance band exercise program had significantly higher life satisfaction levels [ 16 ].…”
Section: Introductionmentioning
confidence: 99%